2016
DOI: 10.1002/ptr.5611
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Androgen Markers Using a Novel Betasitosterol, Thioctic Acid and Carnitine-containing Compound in Prostate and Hair Follicle Cell-based Assays

Abstract: Androgenetic alopecia (AGA) affects approximately 70% of men and 40% of women in an age-dependent manner and is partially mediated by androgen hormones. Benign prostatic hyperplasia (BPH) similarly affects 50% of the male population, rising by 10% each decade. Finasteride inhibits 5-alpha reductase (5AR) and is used to treat both disorders, despite offering limited clinical benefits accompanied by significant adverse side effects. Building on our previous work demonstrating the efficacy of naturally derived 5A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Twenty‐four studies investigated gene expression profiling 18–28 and markers for AGA 29–41 . Fourteen studies focused on the action of 5‐alpha reductase (5AR), which converts the androgen (testosterone) into dihydrotestosterone (DHT) and the inhibition of this enzyme 42–55 using enzymatic, radiochemical and cell proliferation assays. Thirteen studies used the same techniques to investigate the role of other enzymes in the mediation of AGA 4 ,.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐four studies investigated gene expression profiling 18–28 and markers for AGA 29–41 . Fourteen studies focused on the action of 5‐alpha reductase (5AR), which converts the androgen (testosterone) into dihydrotestosterone (DHT) and the inhibition of this enzyme 42–55 using enzymatic, radiochemical and cell proliferation assays. Thirteen studies used the same techniques to investigate the role of other enzymes in the mediation of AGA 4 ,.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some studies used DPCs 43 ,. 45 , 48 , 53 Scalp DPCs are specialized mesenchymal cells of tissues affected by AGA that exist in the dermal papilla located at the basal layer of hair follicles. These cells play a pivotal role in the hair cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Cabeza et al reported the effect of βsitosterol to inhibit 5AR1 in the hamster prostate (38). They The aforementioned study proved that stigmasterol and β-sitosterol targeting 5AR and inflammatory mediators might represent a rational approach in treating AGA and BPH (40). Currently, available drugs for AGA are finasteride and dutasteride, which are synthetic.…”
Section: Discussionmentioning
confidence: 98%